Role of Radiation Therapy for Choroidal Hemangioma: A Brief Review - Kiran Turaka; Aruna Turaka; Bobby N Koneru (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2016)
Choroidal hemangioma is an uncommon benign vascular hamartoma. Depending on the extent of the involved choroid, it can be subtyped into circumscribed form that occurs sporadically as an isolated tumor or a diffuse form that occurs in association with Sturge-Weber syndrome. It appears as an orange-red mass, located commonly posterior to the equator and is mostly asymptomatic. Poor vision is attributed to exudative retinal detachment, cystoid macular edema, foveal distortion and refractive errors. Diagnosis is crucial and is aided by ancillary tests such as ophthalmic ultrasonography, fundus fluorescein angiogram and Indocyanine green angiogram. The aim of treatment is to induce tumor atrophy, resolve the exudates, improve the vision, preserve the overlying retinal function and salvage the globe. Symptomatic tumors are treated by various treatment methods such as laser photocoagulation, transpupillary thermotherapy, photodynamic therapy and radiation therapy. Though external beam radiotherapy is a safe and effective treatment method, radiation induced complications limited its utility. Advanced radiation delivery  techniques (such as proton beam therapy, plaque brachytherapy and stereotactic radiosurgery with Gamma Knife Radiosurgery) precisely target the tumor without damaging surrounding ocular tissues. These focal treatment methods enhance both in regressing the tumor, resolve the subretinal fluid/exudates thereby re-attaching retina and preserve or stabilize the visual acuity. The radiation  induced ocular side effects are less with these newer radiation delivery methods. Anti-vascular endothelial growth factors and oral β-blockers are newer treatment methods available for treating choroidal hemangiomas.